Antarctic EEZ Baselines: An Alternative Formula - Green, J (The International Journal of Marine and Coastal Law, 1996)
The Antarctic has a unique political and physical architecture which is going to be difficult to reconcile with the guidelines and obligations contained within the LOS Convention. This is particularly so in relation to the LOS Convention's rules regarding the delimitation of a baseline from which both the EEZ and continental shelf are measured because of the presence of ice obscuring the true coastline. Of the seven states claiming sovereignty over Antarctic territory, Australia is one which has formally declared an EEZ off its Australian Antarctic Territory. However it has done so without first deciding where its coastal baseline will be positioned. Notwithstanding the possible political ramifications of Australia's pre- emptive declaration, there are choices available for baseline positioning which are not necessarily contained within the LOS Convention but, if treated in the usual consensual manner of Antarctic Treaty Party negotiations and the general rules of international law, represent a possible solution to this dilemma.